Two new species of the genus Paramitraceras Pickard-Cambridge, 1905 (Opiliones: Laniatores: Stygnopsidae) from Chiapas, Mexico - Cruz-López, Jesús A.; Francke, Oscar F. (Zootaxa, 2013)
Paramitraceras pickardcambridgei sp. nov. and Paramitraceras tzotzil sp. nov. from Chiapas, Mexico are described based on specimens previously determined as Paramitraceras granulatum Pickard-Cambridge, 1905 by Goodnight and Goodnight. The male genitalia of the new species and P. granulatum are illustrated with scanning electronic micrographs (SEMs) or drawings derived from them. The importance of the ocular tubercle, cheliceral dentition and sexual dimor-phism, pedipalpal armature and male genitalia as taxonomic characters within the genus is discussed as well as differences and similarities between Paramitraceras Pickard-Cambridge, 1905 and its most similar genus, Sbordonia Šilhavý, 1977.